PENGARUH KARAKTERISTIK INDIVIDU, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR INSPEKTORAT DAERAH PROVINSI SULAWESI TENGAH - Iskandar, Iskandar (Katalogis, 2017)
The objectives of the study are 1.) to define and analyze simultaneous influence of individual characteristics, workloads, and work enviroment on officials performance in The Inspectorate Office of Central Sulawesi; 2.) to define and analyze the influence of individual characteristics on ifficials’ performance in The Inspectorate Office of Central Sulawesi; 3.) to define and analyze simultaneous influence of workloads on officials’ performance in The Inspectorate Office of Central Sulawesi; 4.) to define and analyze simultaneous Influence of work environment on officials’ performance in The Inspectorate Office of Central Sulawesi. The sample in this research consists of 75 officials in The Inspectorate Office of Central Sulawesi who are selected by using census method. Type of research is causal analysis with multiple regressions analysis. The results of the test show that; 1.) individual characteristics, workloads, and work environment simultaneously have significant influence on officials’ performance in The Inspectorate Office of Central Sulawesi with Fvalue of 19.175 on the significant level of 0,000; 2.) Individuals’ characteristics have a positive and significant influence on officials’ performance in The Inspectorate Office of Central Sulawesi sig-t of 0,000<α 0,05; 3.) workloads have a negative and significant influence on officials performance in The Inspectorate Office of Central Sulawesi with sig-t of 0,001<α 0,05; 4.) work environment has a positive and significant influence on officials’ performance in The Inspectorate Office of Central Sulawesi with sig-t of 0,000<α 0,05.